Efficacy of Spironolactone Compared with Doxycycline in Moderate Acne in Adult Females: Results of the Multicentre, Controlled, Randomized, Double-blind Prospective and Parallel Female Acne Spironolactone vs doxyCycline Efficacy (FASCE) Study - Brigitte Dréno; Jean-Michel Nguyen; Ewa Hainaut; Laurent Machet; Marie-Thérèse Leccia; Nathalie Beneton; Jean-Paul Claudel; Philippe Célérier; Marie Le Moigne; Sarah Le Naour; Florence Vrignaud; Alexandra Poinas; et al. (Medical Journals Sweden, 2024)
Acne in adult females is triggered mainly by hormones. Doxycycline is a reference treatment in acne. Spironolactone targets the androgen receptor of sebaceous glands and is prescribed off-label for female adult acne. This multicentre, controlled, randomized, double-blind prospective and parallel study assessed the efficacy of spironolactone compared with doxycycline in adult female acne. A total of 133 women with moderate acne were randomized to receive treatment with: (i) doxycycline and benzoyl peroxide for 3 months followed by a 3-month treatment with its placebo and benzoyl peroxide, or (ii) spironolactone and benzoyl peroxide for 6 months. Successfully treated patients continued with benzoyl peroxide or spironolactone alone for a further 6 months. Primary endpoints were treatment success at month 4 and month 6 with the AFAST score. At all visits, the ECLA score, lesion counts, local and systemic safety and quality of life were assessed. Spironolactone performed better at month 4 and showed a statistically significant better treatment success after 6 months than doxycycline (p = 0.007). Spironolactone was 1.37-times and 2.87-times more successful compared with doxycycline at respective time-points. AFAST and ECLA scores, as well as lesion counts always improved more with spironolactone. Patients' quality of life was better with spironolactone at month 4 and month 6. Spironolactone was very well tolerated. This is the first study to show that, in female adults with moderate acne, treatment with spironolactone is significantly more successful than doxycycline and very well tolerated.